3D graphene oxide supramolecular hybrid hydrogel with well-ordered interior microstructure prepared by a host–guest inclusion-induced self-assembly strategy. Issue 97 (4th October 2016) - Ha, Wei; Yu, Jing; Chen, Juan; Shi, Yan-ping
Abstract : A three-dimensional self-assembly strategy for constructing graphene oxide hybrid supramolecular hydrogel with regular porous structure was developed. Abstract : Here we report a novel strategy for constructing supramolecular hybrid hydrogels with regular porous structure via three-dimensional self-assembly of graphene oxide (GO) and rigid pseudopolyrotaxane (PPR) formed by low-MW linear poly(ethylene glycol) (PEG) threading a series of α-cyclodextrin (α-CD). By the strong π–π interactions between the pyrene group (Py) and GO sheets, the pyrene–poly(ethylene glycol) (Py–PEG) conjugate polymer was successfully adsorbed onto the surface of GO, forming the homogenous layered GO–Py–PEG aggregates induced by parallel arrangement of GO sheets. Subsequently, α-CD was added into GO–Py–PEG hybrids solution, and rigid necklace-like PPR supramolecular structure was formed owing to the PEG chains threading into the cavities of a series of α-CD via the well-known host–guest inclusion interaction. Soon afterwards, 3D supramolecular hydrogel with well-ordered porous structure was formed by virtue of the 3D self-assembly of GO–Py–PEG sheets induced by the strong hydrogen-bond interaction among adjacent rigid PPR. GO–Py–PEG/α-CD hydrogel shows enhanced mechanical property compared with native Py–PEG/α-CD hydrogel and also retains the shear-thinning property. The hybrid hydrogel was further utilized for loading water-soluble drug doxorubicin (DOX), and subsequently the microstructure-dependent drug delivery performance was investigated preliminarily. We believe this study will provide a new insight for designing and constructing supramolecular hydrogels to broaden their breakthrough applications.